KETERAMPILAN VARIASI MENGAJAR DOSEN IAIN KENDARI (Studi Pada Dosen FTIK IAIN Kendari) - Rasmi Rasmi (Tarbiya Islamica, 2020)
This study examines the teaching variation skills of the Lecturers of the Tarbiyah and Teacher Training Faculty (FTIK) IAIN Kendari. The main problems discussed were how to implement the variations in teaching styles of FTIK lecturers at IAIN Kendari? The findings in this study indicate that the skills of variations in teaching styles for the Lecturers of the Faculty of Tarbiyah and Teacher Training, IAIN Kendari, have generally been implemented based on the components of variations in teaching styles but not optimally. Based on the findings, there are still aspects of teaching style that have not been implemented optimally by the Lecturers of the Tarbiyah and Teacher Training Faculty IAIN Kendari. However, a small number or one or two of the lecturers at the Faculty of Tarbiyah and Teacher Training at IAIN Kendari have carried out the learning process in accordance with the skills component of variations in teaching styles. Based on the findings in the research above, it can be argued that the form of developing learning activities is first, the need for policy makers at IAIN Kendari to make related policies on teaching variation skills so that learning can be optimal. Second, it is necessary to hold various teaching skills trainings for junior lecturers and alumni of the Tarbiyah and Teaching Sciences Department of IAIN Kendari before they carry out their duties as teachers. Third, it is necessary to have variations in teaching, especially variations in teaching styles in order to overcome the emergence of boredom and boredom in learning activities by each teacher / lecturer, especially the Lecturers of the Tarbiyah Faculty and Teacher Training, IAIN Kendari.